(3QSGdI aj TghQ GdYGe GdYLei haUhdg hefGRdgs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ai GdSeGA HQhLkG CeG HYO abO SCdJfi CjgG GdCN ai Gddg JYGdi Cf CbjO dc LedI eNJUQI ai TghQ GdYGe GdYLei haUhdg hefGRdg s
(3BNQgG (B:s
(3hcGfhf GdCNjQ hTHGW hBPGQ hfjSGf hBjGQ hMRjQGf hJehR hBH hCjdhd , hChd GdYGe YfOge CcJHQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs